1852 Effect of Conflict Resolution Training on Behavioral Problems in Children in Couples Referring to Counseling Centers in Shiraz-Iran, 2011. (October 2012) - Sharif, F; Solymani, S; Mani, A; Keshavarzi, S
Abstract : Background and Aim: Marital conflicts are among the most common problems in today's society. The impacts of marital conflicts on the children's behavioral problems have also been approved. We aimed to examine the effects of conflict resolution training on the children's behavioral problems in a sample of Iranian couples. Methods: This study performed on 56 couples who had the required criteria & were randomly selected. These couples had moderate to severe conflict scores (60 and over) based on the marital conflict questionnaire. The subjects were divided into two groups, using blocking random allocation. Then the experimental group was randomly subdivided into three groups and received 10 sessions conflict resolution skills training. The level of conflict and child behavioral problems was checked before, immediately, and one month after intervention in the experimental groups. In the control group these amounts were checked before and one month after intervention. Results: In this study both groups were homogenous demographically with no statistically significant differences. Mean score of marital conflict before, immediately, and one month after intervention was statistically significant in men and women (P<0.0001); But not in control group. Mean score of child behavioral problems before, immediately, and one month after intervention was not statistically significant in both groups. Conclusion: Conflict resolution training was effective in reducing marital conflicts. Therefore this method can be recommended for couples.